Enhancing Digital Literacy for Sustainable Economic Development - Rafika Arsyad; Moch. Fathoni; Ardiansah Ardiansah; Kholisatul Amaliyah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study examines the adoption of the Quick Response Code Indonesian Standard (QRIS) as a cross-border digital payment system in Southeast Asia, with a particular focus on Indonesia and Malaysia. It investigates the barriers to QRIS adoption and analyzes how digital literacy can facilitate its implementation in promoting financial inclusion, economic efficiency, and sustainable development. Method: The research employs a qualitative literature review and field observation approach to identify the main obstacles to QRIS adoption and how digital literacy can mitigate these barriers. Results: The findings indicate that inadequate digital infrastructure, cybersecurity concerns, and limited public awareness remain the primary barriers to QRIS adoption. Strengthening digital literacy and cross-border institutional collaboration can increase public trust, encourage QRIS utilization in the tourism sector, and support green economy initiatives by reducing dependence on cash-based transactions. Novelty: The proposed framework integrates digital literacy, cross-border QRIS adoption, and green economy development within the Southeast Asian context. It contributes to the literature by positioning digital literacy as a key driver of sustainable digital payment adoption beyond the technological and financial inclusion perspectives emphasized in previous studies.